A Case Study on the Assessment of Program Quality through CO-PO Mapping and its Attainment - Rajagopal Reddy, B.; Karuppiah, Natarajan; Asif, Md.; Ravivarman, S. (Journal of Engineering Education Transformations, 2021)
In recent years, accreditation of National Board of Accreditation has become mandatory for all the Autonomous colleges and Universities. NBA stresses on Outcome Based Education to improve the quality of education. It has formulated twelve graduate attributes to measure the quality of the program that a graduate has to acquire from any college/university during his four years of under graduation. The success of any program depends on the attainment of course outcomes and program outcomes. But there is a lack of understanding among the Engineering faculties in CO-PO attainment calculations. This study explores the significance of proper CO-PO mapping and its attainment calculation. CO-PO mapping and its attainment calculations are an integral part of OBE and it helps in continuous quality improvement, which serves as a feedback for OBE loop. CQI is instrumental in identifying any setbacks in Teaching Learning Process and additional solutions are figured out to improve the delivery of the course. In this study, different approaches are suggested to calculate the attainment of COs of the course and POs, PSOs of the program. Results and discussions are done on the attainment of COs of different courses and suggestions for the courses which fail to attain the target has been discussed. A sample of CO-PO attainment calculation for the course Basic Electrical Engineering offered for BTech I Year students has been discussed. Microsoft Office Excel spreadsheet has been used for computation purpose.